Family Practices, Holiday and the Everyday. (14th March 2016) - Hall, Sarah Marie; Holdsworth, Clare
Abstract: Holidays are central to the rhythm of everyday family practices and consumption, and are often depicted, within both academic literature and consumer marketing, as a defining moment in contemporary family life. To date, academic accounts of the experiences of travel and tourism have been mostly developed outside of the realm of everyday family practices and intimate relations. In this paper, therefore, we advance an interpretation of family holidays as a constituent of everyday family practices. To do this, we bring together three distinct yet interrelated conceptual frameworks: those of family practices, holiday and the everyday. Presenting and analysing data collected from ethnographic research with six families and exploring the themes of anticipation and utopian family practices, we identify how the notion of family holidays can be used a conduit for realising not only relationality between family members but also as a means of easing out the tensions and aspirations of everyday family life, a way to perfect the everyday and also to make it more palatable.